2014
DOI: 10.1094/pdis-01-14-0094-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report in China of Soft Rot of Ginger Caused by Pythium aphanidermatum

Abstract: Ginger (Zingiber officinale Roscoe) is an important commercial crop planted on more than 13,000 ha annually in Anqiu city, Shandong Province, China. From 2010 to 2011, the incidence of Pythium soft rot disease on cv. Laiwu Big Ginger reached 40 to 75% in Anqiu and yield losses of up to 60% were observed. The disease symptoms included brown spots on ginger rhizomes followed by soft rot, stems and leaves above ground becoming withered and yellow, and water soaking on the collar region. The soft rot did not produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Loss of ginger production by soft rot varies from place to place and ranged between 4-100% [3,35]. Field losses by ginger soft rot have been reported in different countries; for example losses of 25% in Nepal [35], >50% in Fiji [3], 60% in China [21], 90% in India [36] and 100% at some cultivated areas of Australia [3]. In case of storage condition, crop loss due to Pythium in ginger may also be high and ranged between 4 -90% [35,37].…”
Section: Yield Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of ginger production by soft rot varies from place to place and ranged between 4-100% [3,35]. Field losses by ginger soft rot have been reported in different countries; for example losses of 25% in Nepal [35], >50% in Fiji [3], 60% in China [21], 90% in India [36] and 100% at some cultivated areas of Australia [3]. In case of storage condition, crop loss due to Pythium in ginger may also be high and ranged between 4 -90% [35,37].…”
Section: Yield Lossmentioning
confidence: 99%
“…Bihar [16], Kerala [17], Maharashtra [18], Karnataka [11] and in Madhya Pradesh [19]. P. aphanidermatum was also responsible for soft rot of ginger in Australia [5], Bangladesh [20], China [21] and Japan [22]. On other hand, rhizome rot caused by P. butleri was reported in Malabar and South Kanara districts of South India [23].…”
Section: Introductionmentioning
confidence: 99%
“…Pythium aphanidermatum, which cause the rhizome rot disease (Stirling et al, 2009) was first reported in China (Li et al, 2014) is a soil as well as seed borne pathogen which is very destructive to ginger crop and its control became a challenge to society (Jayasekhar et al, 2000). Secretion of cell wall degrading enzymes leads for their successful colonization around rhizospheric zone (Geethu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is also a cash crop for growers in many countries including China, India, Indonesia, Fiji Australia etc (Kavitha and Thomas, 2008). In 2011 the total ginger production in China, the second largest ginger producing country in the world, was 426,032 tons from 36,007 hectare (Li et al, 2014). However, ginger is cultivated, which can lead to the outbreak of soil-borne diseases such as ginger blast, damping-off and anthracnose.…”
Section: Introductionmentioning
confidence: 99%
“…can infect roots, collar, and succulent parts of the rhizome (Stirling et al, 2009), leading to 5 to 30 % yield and even losses, up to 100 % in the case of water logging and high temperatures (Stirling et al, 2009;Wang et al, 2003). Once ginger fields have been infested with Pythium spp., the pathogens could persistent in the soil and lead to ginger soft rot in subsequent replanting (Li et al, 2014). To control ginger soft rot and other soil-borne phytopathogenic diseases, farmers repeatedly apply synthetic, plant protection products to the soil, such as Mefenoxam.…”
Section: Introductionmentioning
confidence: 99%